Optimising Poultry Growth, Health and Economics: The Role of Probiotic Strain Clostridium Butyricum and Lactobacillus Plantarum in Indigenous Naked Neck Chicken Production (SAARC Journal of Agriculture, 2025)
This study investigated the effects of dietary probiotics, Clostridium butyricum and Lactobacillus plantarum, on growth, blood traits, and gut bacteria in Indigenous Naked Neck (INN) chickens. A total of 72 chickens, each 10 weeks old, were randomly assigned to four groups: T0 (control), T1 (6×10⁹ CFU/kg), T2 (7×10⁹ CFU/kg), and T3 (8×10⁹ CFU/kg), with 18 birds in each group. The trial continued for eight weeks. Birds fed with probiotics gained more weight and had better growth performance than the control group. The T1 group showed a 23.5 percent increase in final body weight. Feed conversion ratio (FCR) improved significantly, with the lowest FCR recorded in T1 (5.19), showing better feed efficiency. Fecal bacterial load was reduced by 20.1 percent in the T1 group, indicating improved gut health. Hematological analysis showed that probiotics did not harm the birds. Levels of hemoglobin, red blood cells, and white blood cells remained within normal limits. This confirmed the safety of the probiotics used. Economic analysis revealed that the net farm income (NFI) was 21.9 percent higher in T1 compared to the control. In conclusion, supplementation with Clostridium butyricum and Lactobacillus plantarum at 6×10⁹ CFU/kg improved growth, feed efficiency, gut health, and farm income in INN chickens. These probiotics can be considered a safe and effective alternative to antibiotics in small-scale and sustainable poultry farming systems.SAARC J. Agric., 23(1): 138-153 (2025)